(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2018)
Numbers of connected rods are used in the assembly of petroleum engines, the task of connecting rod important of converting reciprocating motion of the piston into rotary motion of the crankshaft. In this work stress analysis at various individual tensile and compressive loads acting on connecting rod at different speed was done. Simulation was performed by using Cero PTC software to obtain stress distribution in the connecting rod at static condition.